On the uniqueness of the solution of a K. Ito's stochastic equation - Surgailis, D. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Сургайлис. О единственности решения стохастического уравнения К. ИтоD. Surgailis. Apie K. Ito stochastinės lygties sprendinio vienatinumą